Sensitive Voltammetric Determination of Ticlopidine in Pharmaceuticals Employing a Multi-Walled Carbon Nanotubes Paste Electrode - Rebech, Igor; Scremin, Jessica; Tarley, César Ricardo Teixeira; Sartori, Elen Romão (Orbital: The Electronic Journal of Chemistry, 2016)
A sensitive analytical procedure has been developed for the determination of ticlopidine using a multi-walled carbon nanotubes paste electrode (MWCNTsPE). Direct oxidation of analyte was observed by cyclic voltammetry as evidenced by the presence of well-shaped irreversible peak at 1.05 V vs Ag/AgCl (3.0 mol L–1 KCl) in Britton-Robinson buffer solution (pH 5.0). The use of this electrode has been found to influence the electrochemical determination by presenting a higher intensity of oxidation current for ticlopidine and also a lower detection limit. Using differential pulse voltammetric modality, the obtained analytical curve was linear for ticlopidine concentration ranging from 0.75 to 20 µmol L–1, with detection limit of 0.10 µmol L–1. The proposed method was successfully used to determination of ticlopidine in pharmaceuticals, with satisfying results. In order to indicate that the method is of potential application in biological fluids adequate recovery results were obtained for the determination of ticlopidine in synthetic urine sample. DOI: http://dx.doi.org/10.17807/orbital.v8i3.831